Importance of managerial accounting from high growth online company valuation perspective - Jan Pekař (European Financial and Accounting Journal, 2017)
Young, high growth internet/online companies are an attractive topic for market analysts and hot shots of Initial Private Offerings. At the same time, it is very complicated to provide a robust valuation for such companies, as shown by often unpredictable paths of share prices, resulting in the dot.com bubble burst in the past. This paper aims to explain why traditional valuation techniques fail to identify the value of a company with a fair degree of probability and tries to identify new metrics reported by managerial accounting that should be included in the valuation procedure. Assuming the condition of technological interchangeability of processes and practices, the presented paper concludes that using the New Economy specific metrics, such as traffic and various conversion factors explaining top-line traffic monetization, it is possible to adopt a conventional valuation technique, i.e. the DCF, with a very high degree of confidence for the incremental revenue and profit estimations. The interchangeability is also a proof of an innovative potential of the newly introduced technologies and explains the high frequency of strategic acquisitions on this market. Needless to say, the key information sources for valuation of companies under consideration are not financial statements, but managerial records instead, especially web analytics and search algorithm entries.
Keywords: G32; M40; 650; High growth start-up valuation; Online business metrics; Online company valuation